Akuntabilitas Publik Anggota DPD RI dalam Menindaklanjuti Aspirasi Daerah (Studi Kasus Layanan Kesehatan Gratis Masyarakat Banten) - Nurul Agustin; Arief Maulana (Universitas Teuku Umar, 2020)
In the constitutional arrangement of Indonesia, the House of Regional Representative of the Republic of Indonesia (DPD RI) becomes a representative institution that has the task to accommodate regional interests in political decisions. One form of public accountability for members of the DPD RI is to follow up regional aspirations. The problem of the free health service program in Banten Province, which is considered to be in conflict with Law Number 24 of 2011 concerning the Social Security Organizing Agency, examines the quality of the representative functions of DPD RI members as people's representatives in the regional context with the orientation of regional interests. This study aims to explain the roles and obligations of DPD RI members in following up on their regional aspirations. This research was conducted using qualitative methods with a case study approach. The results of this study indicate that the success of DPD RI members' accountability depends on their ability to establish good relationships with executive institutions and local governments. The accountability of DPD RI members is proven in this case because the Ministry of Health is now supporting the Banten Provincial Government's policy to fill a vacancy before all Banten people are registered as National Health Insurance participants.